X Chromosome Inactivation in Opioid Addicted Women - Vousooghi, Nasim (Basic Clin Neurosci, 2015)
INTRODUCTION: X chromosome inactivation (XCI) is a process during which one of the two X chromosomes in female human is silenced leading to equal gene expression with males who have only one X chromosome. Here we have investigated XCI ratio in females with opioid addiction to see whether XCI skewness in women could be a risk factor for opioid addiction. METHODS: 30 adult females meeting DSM IV criteria for opioid addiction and 30 control females with no known history of addiction were included in the study. Digested and undigested DNA samples which were extracted from blood were analyzed after amplification of the polymorphic androgen receptor (AR) gene located on the X chromosome. XCI skewness was studied in 3 ranges: 50:50–64:36 (random inactivation), 65:35–80:20 (moderately skewed) and >80:20 (highly skewed). RESULTS: XCI from informative females in control group was 63% (N=19) random, 27% (N=8) moderately skewed and 10% (N=3) highly skewed. Addicted women showed 57%, 23% and 20%, respectively. The distribution and frequency of XCI status in women with opioid addiction was not significantly different from control group (P=0.55). DISCUSSION: Our data did not approve our hypothesis of increased XCI skewness among women with opioid addiction or unbalanced (non-random) expression of genes associated with X chromosome in female opioid addicted subjects.